Accumulation of 90SR in plant litter of fruit cenosis - V. A. Pogorelova; B. S. Tsipinova; E. A. Melchenko; Yu. N. Ashinov (Новые технологии, 2023)
The growth of industrial and agricultural production, against the backdrop of an increase in the population on the planet, requires an increasing amount of energy. Currently, quite a lot of options for its production are known: thermal and hydroelectric power plants, the use of solar energy (solar batteries), wind, etc. The nuclear power industry continues to develop at a fairly high pace. After the accidents at the Chernobyl nuclear power plant and in Japan, Fukushima 1, a wave of radiophobia rose around the world. But life is taking its toll, and nuclear power plants have already been built or are being built in Belarus, England, China, and so on. Reactors for nuclear power plants are being modernized, but there are no guarantees against accidents. In this case, pollution of various territories, including agricultural land, is possible. The performed scientific work makes a significant contribution to the solution of an urgent problem, i. e. the return of radioactively contaminated fertile lands to agricultural production. The purpose of the research is to study the migration and accumulation of 90Sr in the litter in the orchard, depending on the location of the nuclide in the soil. To achieve the goal of the research, the following tasks have been set: to determine the specific activity of the foliage, bark and wood of the apple tree for the research option with the surface location of the radionuclide on the soil; to determine the specific activity of the foliage, bark and wood of the apple tree for the research option with a buried location of the radionuclide in the soil by 50 cm. To solve the tasks, the field method was used, the radionuclide content in the plant was analyzed on the USK GAMMA Plus device with a beta tract. When the radionuclide is located in the upper part of the soil, the bark of the fruit plant will make the greatest contribution in terms of radiation, followed by leaves and wood. The greatest accumulation of the radionuclide in the second variant of the experiment occurred in the leaves. The difference in the specific activity of 90Sr between foliage and bark in 2016 was 2.0 times, between foliage and wood – 2.2 times. It was established that the studied variants of the experiment had an impact on the accumulation of the pollutant in the plant litter.